2016
DOI: 10.1007/s00408-016-9920-1
|View full text |Cite
|
Sign up to set email alerts
|

Presence of an Alcohol Use Disorder is Associated with Greater Pneumonia Severity in Hospitalized HIV-Infected Patients

Abstract: Purpose Pneumonia is common and more severe in human immunodeficiency virus (HIV)-infected patients. Alcohol consumption in pneumonia patients without HIV is associated with excess mortality and morbidity. However, studies are lacking on the impact of alcohol on pneumonia and HIV. Our goal was to determine if alcohol use was an independent risk factor for pneumonia severity in HIV-infected patients. Methods Secondary analysis of prospective cohort study data evaluating early bronchoscopy for pneumonia diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 36 publications
0
8
2
Order By: Relevance
“…High risk alcohol misuse is an established problem in the HIV population ( Justice et al, 2006 ; Lewden et al, 2005 ). Such alcohol misuse is known to be associated with poor outcomes related to lung infections in HIV patients ( Jolley, Alkhafaf, Hough, & Welsh, 2016 ). Recent studies implicate the effect of alcohol on altering gut microbiota as a mechanism for this HIV-associated susceptibility to lung infection ( Samuelson et al, 2019 ).…”
Section: Auds and Lung Diseasementioning
confidence: 99%
“…High risk alcohol misuse is an established problem in the HIV population ( Justice et al, 2006 ; Lewden et al, 2005 ). Such alcohol misuse is known to be associated with poor outcomes related to lung infections in HIV patients ( Jolley, Alkhafaf, Hough, & Welsh, 2016 ). Recent studies implicate the effect of alcohol on altering gut microbiota as a mechanism for this HIV-associated susceptibility to lung infection ( Samuelson et al, 2019 ).…”
Section: Auds and Lung Diseasementioning
confidence: 99%
“…Heavy drinking in this population is also associated with engagement in risky health behavior, such as cigarette (18,19) and substance use (20), which can lead to other chronic illnesses. Some studies have found that PLWH who use alcohol have increased chronic comorbidity (5,10,21,22), while other studies have found no such association (3,2325). Others have found a J-curve association between alcohol consumption and risk for chronic illness.…”
Section: Introductionmentioning
confidence: 99%
“…Alcohol use is common among persons living with HIV (PLWH) and is reported among 39–81% (15). Prevalence of heavy drinking has been reported in as much as 25–45% (1,6,7) of PLWH, with alcohol dependence ranging from 5.5 to 10% (4,810). Alcohol consumption, in general, is negatively associated with completing the steps of the HIV care continuum (11) and heavy alcohol use is associated with poor retention in HIV care and lower visit adherence, compared to those who do not drink 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Non-hazardous alcohol consumption once per week or more was reported to decrease survival in PLWH by 1 year, and by 6.4 years for those with daily hazardous consumption (38). In addition, alcohol consumption independently increases the risk for several comorbidities in PLWH, including the risk of dementia (8), cardiovascular disease (39,40), hepatic cirrhosis (41), and pneumonia (42). A study by Freiberg et al, showed that compared with infrequent and moderate drinking, hazardous drinking and alcohol abuse were associated with a higher prevalence of cardiovascular diseases (39).…”
Section: Alcohol Use Accelerates the Progression Of Hiv Infectionmentioning
confidence: 99%